Peran Kepala Desa Dalam Meningkatkan Pelayanan Publik Desa Karang Tunggal - Helmi; Sudarno; Ria Trisnomurti (LPPM STIH Awang Long, 2019)
This study uses an empirical legal research method using an individual personality approach in order to determine the role of the village head in improving public services at the Karang Tunggal Village Office, located in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. Sources of data used in this study use primary data sources and secondary data sources. The collection technique used in this research is observation, document study, literature study and interviews. Data analysis used qualitative analysis which presented descriptively. Public services are one of the variables that measure the success of an organization, if the public services performed are of the best quality, the implementation of these services can be said to be successful and successful in a service implementation. The description based on the results of this study is that the Head of Karang Tunggal Village plays a major role in improving public services at the Karang Tunggal Village Office by paying attention to service quality, improving the performance of Village officials, improving human resources of Village officials, public service ethics, service management concepts, excellent service in public services, and supervision of public services.